Iatrogenic acquired factor V inhibitors: A case report and review of the French pharmacovigilance database. Issue 157 (September 2017) - Theron, Alexandre; Burcheri, Sara; Vacheret, Fabienne; Hillaire-Buys, Dominique; Sauguet, Pauline; Schved, Jean-François; Faillie, Jean-Luc; Biron-Andreani, Christine
Highlights: Clinicians should watch for drug-induced coagulation factor inhibitors. Acquired FV inhibitors are an heterogeneous disease. Antibiotics are the most frequent drugs associated with acquired FV inhibitors. Optimal management in asymptomatic patients with acquired FV inhibitors is difficult.